2020
DOI: 10.1371/journal.ppat.1008286
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of HIV DNA reservoir seeding in a cohort of superinfected Kenyan women

Abstract: Cancer Consortium, and P30 AI027757 CFAR New During HIV infection, a reservoir of long-lived latently infected cells is established that persists during antiretroviral therapy (ART) and is the source of virus replication after treatment cessation. A better understanding of when viruses enter the HIV reservoir (reservoir seeding) will aid efforts to target these long-lived HIV infected cells during their establishment. We studied women infected at two different times with two genetically distinct HIV strains (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
99
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(126 citation statements)
references
References 36 publications
21
99
2
Order By: Relevance
“…Both the stability of the HIV-1-specific T cell response and the comparable level of population-level virus escape in treated and untreated individuals is consistent with studies of HIV-1 reservoir formation and kinetics. These studies showed that the HIV-1 reservoir is mostly formed at the time of ART initiation ( Brodin et al, 2016 ; Abrahams et al, 2019 ; Pankau et al, 2020 ) and its subsequent rate of decay is very slow ( Crooks et al, 2015 ; Siliciano and Siliciano, 2015 ; Siliciano and Siliciano, 2004 ), with only limited variation in the number of proviruses, or the types of proviral defects observed in PLWH on ART over time ( Lu et al, 2018 ). More recently, longitudinal analyses of near full-length proviral sequences in PLWH on ART showed no enrichment in escaped epitopes over time suggesting that HIV-1-specific T cells do not significantly alter the provirus landscape in people durably suppressed ( Antar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the stability of the HIV-1-specific T cell response and the comparable level of population-level virus escape in treated and untreated individuals is consistent with studies of HIV-1 reservoir formation and kinetics. These studies showed that the HIV-1 reservoir is mostly formed at the time of ART initiation ( Brodin et al, 2016 ; Abrahams et al, 2019 ; Pankau et al, 2020 ) and its subsequent rate of decay is very slow ( Crooks et al, 2015 ; Siliciano and Siliciano, 2015 ; Siliciano and Siliciano, 2004 ), with only limited variation in the number of proviruses, or the types of proviral defects observed in PLWH on ART over time ( Lu et al, 2018 ). More recently, longitudinal analyses of near full-length proviral sequences in PLWH on ART showed no enrichment in escaped epitopes over time suggesting that HIV-1-specific T cells do not significantly alter the provirus landscape in people durably suppressed ( Antar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…ART is highly effective in inhibiting viral replication with multiple studies reporting that HIV-1 does not undergo directional selection during suppressive ART ( Kearney et al, 2014 ; Kearney et al, 2016 ; Rosenbloom et al, 2017 ; Van Zyl et al, 2017 ). Recent studies have reported that the majority of proviruses, both total HIV-1 DNA and replication-competent viruses, that persist during ART, reflect viruses circulating during the year prior to ART initiation ( Brodin et al, 2016 ; Abrahams et al, 2019 ; Pankau et al, 2020 ). These studies suggest that ART initiation is the major driver of latency formation, including the formation of the replication-competent stable HIV-1 reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…The HIV reservoir is established early during primary HIV infection [30,31]. However, in the untreated infection, the reservoir seems to turn over rather quickly, and most proviral DNA sequences in peripheral blood mononuclear cells from ART-treated individuals were recently shown to match circulating HIV variants detected shortly before the start of therapy [32][33][34][35]. In most subjects, the HIV DNA load decreases during the first year after ART initiation, but the decay slows down during years 1-4, and the HIV DNA load eventually reaches a plateau [36].…”
Section: Persistence Of Hiv Reservoirs On Artmentioning
confidence: 99%
“…Further, based on detailed phylogenetic analyses, Abrahams et al (2019) were able to show that approximately 80% of the replication-competent reservoir appeared to originate from viruses circulating in the plasma in the year prior to ART, although a minority of vial genomes were found in the reservoir that were closely related to viruses circulating much earlier in untreated infection. Most recently, a third cohort demonstrated very similar findings (Pankau et al, 2020).…”
Section: The Latent Reservoir Is Unexpectedly Dynamicmentioning
confidence: 61%